On the Development of a Nomogram for Alkali Activated Fly Ash Material (AAFAM) Mixtures - Partogi H. Simatupang; Iswandi Imran; Ivindra Pane; Bambang Sunendar (Journal of Engineering and Technological Sciences, 2015)
Alkali activated fly ash material (AAFAM) has become the most promising material to substitute materials based on ordinary Portland cement (OPC). However, there is no available nomogram for AAFAM mixtures. In contrast, there are many rational methods available in the literature to make paste, mortar and concrete with OPC based materials, such as Monteiro-Helene's nomogram, which uses Abram's law, Lyse's law and Molinari's law. This paper presents a study to construct such a nomogram for AAFAM mixtures by first conducting experiments on the  paste and mortar phases. The procedure of Monteiro-Helene's nomogram was adopted in this formulation. The first step in this direction was to find a close relationship between the strength and paste composition of the material that can be used as a substitute for Abram's law. The second step  was  to construct the equivalent  of  Lyse's and Molinari's relationships by varying the sand and fly ash contents. The results show that it is possible to make a nomogram for AAFAM mixtures such as the one for OPC based materials. Class F fly ash and its mortar phase were used to construct the nomogram. In addition, the  mortar  samples  that were  used to build the nomogram had similar solidification products according to their microscopic characteristics.